1988
DOI: 10.1080/15287398809531163
|View full text |Cite
|
Sign up to set email alerts
|

Oral toxicity of a bloom of the cyanobacteriummicrocystis aeruginosaadministered to mice over periods up to 1 year

Abstract: Cyanobacterial blooms in lakes have been reported causing livestock deaths and liver injury to human populations. In this study bloom material consisting of Microcystis aeruginosa was collected from a farm water storage after the death of sheep drinking from it. The cyanobacterial cells were lysed and a cell-free extract was provided to mice at a series of dilutions as their only source of drinking water. Mice of both sexes, with controls, were killed at intervals up to 1 yr of administration. Autopsies, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 9 publications
2
53
0
4
Order By: Relevance
“…PCNA can associate with several procaspases to block their activation for presenting anti-apoptotic activities [73,74]. These reports and the present results altogether suggest that MCs may induce apoptosis and inflammatory in the brain [12,13].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…PCNA can associate with several procaspases to block their activation for presenting anti-apoptotic activities [73,74]. These reports and the present results altogether suggest that MCs may induce apoptosis and inflammatory in the brain [12,13].…”
Section: Discussionsupporting
confidence: 62%
“…More recently, several OATPs/Oatps (rodent Oatp) appear to be specifically required for the active uptake of MCs into brain [10][11][12]. In fish, Baganz et al reported changes in the spontaneous locomotor behavior of zebrafish (Danio rerio) and sunbleak (Leucaspius delineatus) after MCLR exposure [13,14] and Cazenave et al showed changes in swimming activity of Jenynsia multidentata fed with microcystin-RR (MCRR) [15], suggesting the probable neurotoxicity of MCs. In mammals, spatial learning and memory loss were observed in rats after intra-hippocampal infusion with MCLR [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the major target organ for microcystin toxicity; it was shown to accumulate 20-70% of a radioactively labeled toxin dose (intravenous) (48)(49)(50)(51)(52)(53)(54). Studies in mice and pigs exposed to extracts of a toxic M. aeruginosa bloom demonstrated dosedependent toxicity (55,56). Increased mortality, liver weight, and plasma alanine aminotransferase levels were associated with loss of body weight.…”
Section: Cylindrospermopsinmentioning
confidence: 99%
“…The waterblooms of toxic cyanobacteria (blue-green algae), found in eutrophic freshwater municipal and residential water supplies, are an increasing environmental hazard in several areas of the world (Francis 1878;Carmichael 1988;Falconer et al 1998). Microcystins are cyclic heptapeptides containing two variable l-amino acids and an unusual amino acid, 3-amino-9-methoxy-10-phenyl-2,6,8-trimethyl-deca-4,6-dienoic acid (Adda) (Fig.…”
Section: Microcystinsmentioning
confidence: 99%